The colexification of vision and cognition in Mandarin: controlled activity surpasses uncontrolled experience - Dai Ying; Wu Yicheng (Cognitive Linguistics)
Given the colexification of perception and cognition, Georgakopoulos et al. (2022. Universal and macro-areal patterns in the lexicon: A case-study in the perception-cognition domain. Linguistic Typology 26(2). 439–487) claim that uncontrolled experience rather than controlled activity has a direct linkage to cognition. To test whether this is a universal tendency, this study conducts a contrastive behavioral profile analysis of two basic vision verbs in Mandarin: kàn, a controlled activity verb, and jiàn, an uncontrolled experience verb. The results show that (i) both kàn and jiàn colexify visual activity and cognitive senses; (ii) kàn is able to express a wider range of cognitive meanings, i.e., know, understand, and think, whereas jiàn only extends into know; and (iii) visual and cognitive meanings have more proximal relationships in the colexification pattern of kàn than that of jiàn. The study confirms the universality of the colexification between vision and cognition while providing counterexamples to the above-mentioned large data-based findings. Accordingly, a dichotomy of controlled activity versus uncontrolled experience is proposed for the colexification of vision and cognition in cognitive typology.